(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The advancement of tidal technology requires accurate yet computationally efficient simulations to analyse turbine performance. Mid-fidelity tools offers low computational cost with increased accuracy compared to low-fidelity tools from its ability to capture more physical phenomena. This study investigates the development of a mid-fidelity simulation strategy to design and analyse hydro-elastic behavior of flexible tidal turbine blades. Flexible blade in this research implies bend-twist coupling designed to achieve torsional deformation. However, a traditional stiff blade was modelled to analyse the effects of considering elastic modelling. OpenFAST was used to perform coupled hydrodynamic and structural elastic modelling, complemented by one-way fluid-structure interaction (FSI) simulations in ANSYS. The results indicate that considering blade flexibility has minor impact on power coefficient Cp, with maximum values of 0.459 and 0.461 for rigid and elastic simulation respectively, at an optimal tip-speed ratio (TSR) of 6.8. However, maximum thrust coefficient Ct increased from 0.91 to 0.94 when elastic modelling was considered. Increasing inflow angles from 0° to 30° led to reduced hydrodynamic loading and smaller deflections. However, the impact of inflow angle is not well captured using rotor-averaged parameters, highlighting the importance of conducting fatigue assessments. A novel mid-fidelity method of designing and analysing flexible blades have been developed, allowing hydrodynamic/structural analysis. The findings demonstrate that mid-fidelity simulations provide an efficient yet reliable approach for preliminary blade design and performance evaluation. Future work will focus implementation of geometrically exact beam theory (GEBT) for increased fidelity of hydro-elastic analysis, and methodology of designing flexible blade.